A triple‐component deep inferior epigastric artery perforator chimeric free flap for three‐dimensional reconstruction of a complex knee defect complicated with patella osteomyelitis. Issue 4 (25th December 2020) - Yamamoto, Takumi; Yamamoto, Nana
Abstract: Reconstruction of a complex knee defect is challenging, especially when complicated with osteomyelitis. Complex knee defect requires multi‐component three‐dimensional reconstruction using a chimeric flap. Although anterolateral thigh (ALT) flap is the most workhorse chimeric flap, another chimeric flap is required when ALT flap is not available. In this report, we present a case of complex knee defect successfully treated with a free triple‐component chimeric deep inferior epigastric artery perforator (DIEP) flap transfer. A 36 year‐old male sustained right above‐knee amputation and Gustilo IIIB open fracture of the left patella after being run over by a train. Stump formation was performed for the right limb amputation, and the left knee wound resulted in skin necrosis complicated with patella osteomyelitis. After debridement, the left knee wound showed a 3 × 2 cm articular capsule defect, 5 × 2 cm exposed patella stump, and a 16 × 9 cm skin defect. A triple‐component chimeric DIEP flap, containing a 7 × 3 cm rectus abdominis muscle (RAM), a 3 × 2 cm RAM's fascia, and a 23 × 10 cm skin was transferred. The RAM's fascia was used to reconstruct the joint, the RAM to cover the exposed patella's stump and the reconstructed joint, and the skin paddle to cover the skin defect. Six months after the surgery, the patient could walk without osteomyelitis recurrence, and there was no limitation in the left knee joint's range of motion. Although indication is limited, a multi‐component chimeric DIEP flap may be an option for three‐dimensional reconstruction of a complex defect.